Typology of The Coastal Countryside in Supporting Development of North Coast Region in West Java - Apriadi Budi Raharja; Supratognyo Aji; Deden Syarifudin (TATALOKA, 2020)
The pressure from rapid development causes condition of resources and living quality to be less than ideal for future development. The economic characteristics of northern coast regions of West Java commonly deals with fish farm, ground fish catch, industrial area, ship repair, and tourist. This study aimed to reveal the typology of rural area, north coast of West Java province. The analysis used was multivariate to identify a group of objects that have the semblance of a characteristic parameter based on natural resources and human resources. Research locus on six counties that consist of 124 identified villages is a village along northern coast of West Java. Based on analysis of rural typology, four of the rural types were found, namely; typology 1 (comprised 55 villages); typology 2 (48 villages); typology 3 (10 villages); typology 4 (11 villages). Coastal villages of Pantura have a fast transition, However the transition occurred tends to shape village’s characteristic and still unable to improve service quality and quality of life of rural communities.